Research on Experiential Tourism Route Planning Based on Multi-source Data Algorithm in Rich Energy and Cultural Resources Areas. Issue 2 (October 2020) - Yu, Chunyu; Zhang, Heming
Abstract: Historical blocks are the carrier of urban history and culture, reflecting the continuation and development of urban history and culture, embodying a local historical context and regional cultural characteristics, and are an important part of historical and cultural cities. Taking the ancient city of Xi'an as the research area, this paper discusses the design method of the cultural promenade in the ancient city from the aspects of development condition analysis, route selection, theme determination, spatial organization and support system, etc., relying on multi-source data algorithms, and designed 4 Special theme promenade, on this basis, summarizes the planning and design methods of cultural promenade.